Personal Metaphors as Motivational Resources: Boosting Anticipated Incentives and Feelings of Vitality Through a Personal Motto-Goal - Dyllick, Thomas H.; Dickhäuser, Oliver; Stahlberg, Dagmar (Frontiers in Psychology, 2021)
Motto-goals describe a desired mind-set and provide a person with a guiding principle of how to approach a personal goal or obligation (e.g., with the inner strength of a bear I am forging ahead). We propose that motto-goals can be conceptionalized as individually created metaphors and that the figurative, metaphorical language and the characteristics of the formation process make them effective in changing the perception of unpleasant personal obligations as more inherently enjoyable and raise vitality levels. To test whether a newly devised minimalistic motto-goal intervention can make goal striving more attractive (stronger anticipation of activity related incentives) and energize goal-oriented action (increase vitality) in relation to an unpleasant obligation, two experimental studies were conducted. In Study 1 the motto-goal condition led to stronger anticipation of activity related incentives and vitality compared to a distraction task. The effect on vitality was partially mediated by a change in feelings of autonomy. Study 2 replicated the effects compared to a placebo intervention and further found motto-goals to be specifically effective in increasing the anticipation of activity related incentives as opposed to outcome related incentives. The results support that applying motto-goals built with a newly developed minimalist motto-goal intervention can influence the subjective experience of individuals faced with a previously unpleasant obligation.